School location, gender and teaching methods as predictors of primary 5 pupils’ learning outcome in mathematics (2014)
Numerous instructional strategies have been used by researchers to find solution to learners' poor performance in Mathematics. It is observed that the use of these instructional strategies have been neglected in schools. There is the need to look for more proactive methods that will make pupils learn profitably and more friendly. Therefore, this study investigated the effects of Personalised System of Instruction (PSI), Direct Instruction (Dl) and Conventional method (CM) on pupils' achievement in Mathematics in Oyo State. This study adopted a 3x2x2 combination of the pretest-posttest and control group design, randomized, quasi-experimental design in which the treatment operates at three levels [Personalized System of Instruction (PSI) , Direct Instruction (Dl) and Conventional Method (Control)] crossed with gender (male and female), and school location (rural and urban). Purposive sampling was used to select four local government areas in Oyo State, this was to ensure that all the selected local government areas were not clustered in one educational zone. Simple random sampling was used to select 16 primary five classes in 8 urban and 8 rural locations and the pupils constituted the study sample. The instrument used in the study was Mathematics Achievement Test (MAT) (r=0.82). The data generated were analysed using analysis of co-variance (ANCOVA) tested at 0.05 level of significance. Treatment (F(23a4)=183.409), gender(F(13B4)=7.081) and school location (F(13B4)=59.753) had significant main effects on pupils' achievement in Mathematics. A significant difference existed in the achievement scores in Mathematics between the participants in Dl (x=79.8), PSI (x=50.6) and Control (x=38.9). A significant interaction effect of treatment and school location (F(2.3M)-1 7- OO4) listed on pupils' achievement in Mathematics. The adoption of Dl for the improvement of learners' performances was recommended. Learners should be encouraged to work together and help one another in a manner that tends to promote more positive self-evaluations of capability and higher academic attainments than individualistic or competitive ones. Mathematics teachers should give opportunities to all pupils irrespective of their school location and gender so that they are exposed to active learning techniques of PSI and Dl especially when treating difficult mathematics concepts and problems.